Mass Transport Induced by Heat Current in Carbon Nanotubes. (8th December 2013) - Zhong, Wei-Rong; Xu, Zhi-Cheng; Yang, Ming-Ming; Ai, Bao-Quan
Abstract : Transport of helium atoms in the carbon nanotubes is investigated in the presence of temperature gradients. The heat current flowing along the carbon nanotubes can induce a stable directed transport of helium; it is demonstrated that the heat current density rather than the temperature gradient performs as a fundamental physical factor to the mass transport. We provide an alternative route to control the mass transport by using heat. Our results reported here are also relevant for understanding the transition from thermal energy to mechanical energy.